Efficient lignin extraction from oil palm empty fruit bunches using guanidine-based deep eutectic solvents under microwave assistance - Muhammad Nor Arifin, Yaakob; Nurjannah, Salim; Siti Noor Hidayah, Mustapha; Izan Izwan, Misnon; Mohd Hasbi, Ab Rahim; Rasidi, Roslan (Elsevier Ltd, 2024)
The abundance of oil palm empty fruit bunches (OPEFB) in Malaysia necessitates effective waste management strategies. Deep eutectic solvents (DES), particularly chloride-based ones like guanidine hydrochloride (GHCl), offer green and economical pretreatment options for lignocellulosic biomass, enhancing lignin extraction. To the best of current knowledge, no prior investigations have focused on the properties of lignin extracted using this DES system. Therefore, this study investigates the efficient extraction of lignin from oil palm empty fruit bunches (OPEFB) utilizing guanidine-based deep eutectic solvents (GHDES) under microwave assistance. Guanidine hydrochloride (GHCl) is introduced as a hydrogen bond acceptor (HBA) in DES formation, particularly in the GHCl:lactic acid (LA) system. The study systematically investigates the influence of different pretreatment parameters (time and temperature) on the structure and properties of the extracted lignin. Remarkably, guanidine-based DES shows exceptional effectiveness in disrupting the OPEFB structure, resulting in highly efficient lignin extraction. Analyzes show that the DES-extracted lignin has comparable properties to other DES systems, with consistent structural and thermal properties observed at various reaction temperatures and times. Notably, the extracted lignin at 120 °C for 30 min exhibited high yield, minimal impurity content, significant phenolic content, and reduced weight loss. This study not only contributes to the sustainable use of lignin but also highlights the versatility of guanidine-based DES in the utilization of lignocellulosic biomass. The promising results position guanidine-based DES as a viable and innovative candidate for lignin extraction in various applications and promote progress in the utilization of renewable biomass resources.